Literacy-Based Differentiation Learning: Learning to Write Neatly for Students of Class Xi Smkn 1 Technology and Engineering Keerom - Jamlean, Leonora Genoveva (Electronic Journal of Education, Social Economics and Technology, 2025)
This research explores the application of literacy-based differentiation learning to enhance writing skills among SMKN 1 Keerom, Papua students. The study addresses challenges in proper capitalization, spelling, and using capital and lowercase letters in students' writing. A qualitative approach was employed, involving observations, written work analysis, and feedback from teachers and students. The findings indicate that many students struggle with these basic writing skills due to informal speech habits and limited exposure to formal writing education. In response, additional learning time was provided to reinforce these skills. The results demonstrate that students significantly improved their writing accuracy with consistent, creative interventions. This study emphasizes the importance of personalized, project-based learning in fostering better writing habits. The integration of these strategies aligns with the Merdeka Curriculum's goal to enhance literacy, critical thinking, and character development. The research also underscores the role of collaborative efforts between educators and parents in achieving long-term educational success.